STATISTICAL STUDY ON THE USE OF DENTAL LASER IN ENDODONTICS - Adrian Ştefan Stănuşi; Adrian Camen; Oana Andreea Diaconu; Dana Maria Albulescu; Adina Turcu; Andreea Nicola; Cristian Petcu; Lelia Mihaela Gheorghiță; Ruxandra Voinea Georgescu; Mihaela Jana Tuculină (Romanian Journal of Oral Rehabilitation, 2022)
The dental laser can be used in many stages of endodontic treatment, but researchers in the field claim that this device is especially useful for cleaning and decontaminating root canals. Aim of the study The aim of this study was to establish the level of knowledge of Romanian dental practitioners about laser-assisted endodontics, as well as to determine whether the current gold standard in endodontics is respected by them. Material and methods To accomplish this, we completed an electronic questionnaire using Google Forms, which included 20 questions on laser-assisted endodontics, protocol of use and side effects, and the application of modern chemo-mechanical treatment. The questionnaire was distributed online to dentists in Romania. Results Almost all participants stated that they know the laser is used during endodontic treatments, but about half of them do not know if the therapeutic effects reach the less accessible areas of the root canals. Conclusions Our study demonstrated a moderate level of knowledge of laser-assisted endodontics, requiring further studies and the introduction of subjects related to laser technology in the university curriculum.